PENERAPAN HUKUM ADAT DALAM PENYELESAIAN PERSELISIHAN DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Taramadina, Nivia; Ismi, Hayatul; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Law has always existed in every society. In the Kenegrian Empat KotoGunung area, Gunung Toar District, Kuantan Singingi Regency, people still usetheir customary law in resolving disputes. Concretely, dispute resolution withcustomary law is carried out with the principle of peace. The settlement of thecase is carried out by consensus and settlement in stages from the low (mamakkaum) to the high (customary chief). The objectives of writing this thesis are:First, to find out the process of resolving criminal cases based on applicablecustomary law, second to find out the application of customary law in resolvingdisputes in Gunung Toar District.This type of research uses sociological research methods directly at thelocation or place to be studied. This research was conducted in Kenegrian EmpatKoto Gunung Gunung Toar District. While the population and sample are allparties related to the problems examined in this study, the data sources used areprimary data, secondary data and tertiary data, data collection techniques in thisstudy are interviews and document studies.The results of the research The community in Gunung Toar Subdistrictalways prioritizes deliberation in every activity, especially in matters relating tothe settlement of disputes or disputes, so that every problem that occurs in thecommunity always involves the role of traditional leaders in its resolution, this isa reflection of the customs that they have always applied, where every disputealways uses peace efforts with mediation by the perpetrator who has violatedcustomary provisions. The application of customary law in resolving disputesmeans that the case will be resolved in a family manner. For the people ofGunung Toar, customary law is an umbrella for justice seekers and protectseveryone from injustice. Any problems concerning life between fellowcommunities are resolved by customary law.Keywords: Customary Law-Disputes-Customary Rules